Serum and urine TNF-like weak inducer of apoptosis, monocyte chemoattractant protein-1 and neutrophil gelatinase-associated lipocalin as biomarkers of disease activity in patients with systemic lupus erythematosus - MİRİOĞLU, ŞAFAK; Mirioglu, ŞAFAK; ÇINAR, Suzan; YAZICI, Hülya; Ozluk, Y.; KILIÇASLAN, Işın; GÜL, Ahmet; Ocal, L.; İNANÇ, Murat; Artim-Esen, B. (My University, 2020)
Objectives